Determination of Employee Engagement: Analysis Path Career, Organization Culture, Remuneration, and Development Leadership - Setiyarti, Tettie; Subagio, Mochammad; Suryaningsih, Lilik; Sugiarti, Sugiarti; Mahendra, Denny (Green Publisher, 2024)
The purpose of this literature research is to build a hypothesis regarding the influence between variables that can later be used for further research in human resource management. The literature review research article on Employee Engagement Determination: career path analysis, organizational culture, remuneration, and Leadership Development is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Career Path affects Employee Engagement; 2) Organizational Culture affects Employee Engagement; 3) Remuneration affects Employee Engagement; and 4) Leadership Development influences Employee Engagement.